Pengaruh Metode Pembelajaran Mind Mapping Terhadap Hasil Belajar Siswa Pada Materi Sistem Pernapasan Manusia - Jeferson Ndawa Lu; Vidriana Oktoviana Bano (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
The use of learning methods that are not suitable for learning material causes the expected learning objectives to be not achieved so that it has an impact on low student learning from the posttest scores showed that the average value of the experimental class was higher than that of the control class, namely 80 > 70. In addition, from the results of the independent outcomes. One of the efforts made is the use of the mind mapping method. This study aims to determine the effect of the mind mapping learning method on student learning outcomes in class XI IPA at SMA Negeri 3 Waingapu. This type of research is quasi-experimental using a nonequivalent control group research design with a quantitative approach. Sampling using purposive sampling. The population in this study were students of class XI IPA in the even semester of the 2022/2023 academic year. The sample of this study were 35 students of class XI IPA 2 as the control class and 35 students of XI IPA 1 as the experimental class. The results of the analysis obtained sample t-test hypothesis testing, it was obtained a sig (2-tailed) value of 0.000 <0.05, it can be concluded that the mind mapping learning method has an effect on student learning outcomes.